Cover: (View 1/2020). Issue 1 (23rd March 2020) - Unknown
Abstract : Bacteria inhibition is universally required in clinics and daily wellness. Herein, novel gold nanoreactors are designed as a multifunctional platform for the in vivo capture and inhibition of bacteria. The gold nanoreactors facilitate targeted adhesion on bacteria due to targeted surface affinity and nanoscale surface roughness. Moreover, the nanoreactors enable long‐term antibacterial effects under the laser illumination, due to the photothermal ablation mediated by gold nanoparticles. Taking this as an example, the engineering and designing of precision biomaterials allow closer clinical transitions towards personalized medicine.